Effect of annealing atmosphere on the structural and electrical properties of BiFeO3 multiferroic ceramics prepared by sol–gel and spark plasma sintering techniques. Issue 6 (1st May 2016) - Wang, Ting; Song, S.-H.; Wang, Meng; Li, J.-Q.; Ravi, M.
Abstract: Phase-pure BiFeO3 powders were synthesized by sol–gel technique. Based on these powders, high-density BiFeO3 ceramics were prepared by spark plasma sintering (SPS) at 700 °C along with annealing for 2 and 4 h, respectively, at 650 °C under atmospheres of air and oxygen. X-ray diffraction analysis revealed that the 4 h-oxygen-annealed sample contained a single rhombohedral perovskite phase while the samples annealed in the other conditions contained small quantities of impurity phases besides the rhombohedral perovskite phase. The relative density of the 4 h-oxygen-annealed sample was about 96%, being apparently higher than that of the other samples. In comparison with the 4 h-air-annealed sample, the dielectric constant of the 4 h-oxygen-annealed sample was relatively higher. The activation energy for electrical conduction was about 1.17 eV for the 4 h-oxygen-annealed sample while it was about 0.98 eV for the 4 h-air-annealed sample, showing that the former would have a lower room-temperature conductivity ( 2.6×10 −14 S cm −1 ) than the latter ( 2.1×10 −13 S cm −1 ). It is therefore anticipated that the oxygen-annealed sample could possess better ferroelectric properties as compared to the air-annealed sample.